2022
DOI: 10.3389/fmolb.2022.868460
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Formulation Choices on the Freeze-Drying of an Interleukin-6 Reference Material

Abstract: Formulation is critical to successful delivery of lyophilized biologics. We have compared the impact of buffer choice and the addition of sodium chloride (a formulant often viewed as unfavorable for freeze-drying applications) on the outcome of trial lyophilization of an interleukin-6 reference material. While phosphate buffer was a preferred choice and yielded well-formed cakes associated with fair recovery of biological activity, the resultant residual moisture content was high (2–4% w/w). By inclusion of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The addition of ionic salts, such as NaCl, is considered critical in a lyophilization process [122] because it may also negatively affect the freeze-drying process. In some cases, however, the addition of NaCl improves the appearance of the cake of the freeze-dried materials without affecting its bioactivity [123]. For BoNT/A, it was reported that the presence of NaCl during the freeze-drying process results in a loss of bioactivity [124].…”
Section: Naclmentioning
confidence: 99%
“…The addition of ionic salts, such as NaCl, is considered critical in a lyophilization process [122] because it may also negatively affect the freeze-drying process. In some cases, however, the addition of NaCl improves the appearance of the cake of the freeze-dried materials without affecting its bioactivity [123]. For BoNT/A, it was reported that the presence of NaCl during the freeze-drying process results in a loss of bioactivity [124].…”
Section: Naclmentioning
confidence: 99%